Characteristics of the cardiosplenic axis in patients with fatal myocardial infarction - Kercheva, Maria; Ryabov, Vyacheslav; Trusov, Andrey; Stepanov, Ivan; Kzhyshkowska, Julia (Life, 2022)
Myocardial ischemia triggers neurohumoral activation of the cardiosplenic axis. In rodents, adverse outcomes occur upon prolonged entrance of mononuclear cells from the spleen into myocardial tissue. The purpose of this study is to assess the features of spleen structure in patients with fatal myocardial infarction (MI), the dynamics of macrophage infiltration of the spleen and its relationship with cardiac macrophage infiltration and unfavorable outcomes. Using immunohistochemistry techniques, we analyzed the macrophage infiltration of the spleen and myocardium sections collected from patients (n = 30) with fatal MI. The spleen of the patients was decreased and showed a predominance of red pulp with a high concentration of CD68+ and stabilin-1+ cells. The white pulp contained many medium and small follicles and a lower concentration of CD68+ and stabilin-1+ cells, which was comparable to that in the infarct area of the myocardium. The concentration of CD68+ and stabilin-1+ cells increased in the myocardium in the late period of MI, but did not show any dynamics in the spleen. A high number of CD68+ cells in the red pulp and reduced concentration of stabilin-1+ cells in the white pulp were associated with unfavorable post-infarction outcomes. These fundamental findings could be a basis for the development of new personalized therapeutic and diagnostic approaches for the treatment of MI and its complications.
Gesehen am 26.02.2024
Dieser Artikel gehört zum Special issue: The molecular mechanism of cardiovascular disease